Ethnomathematics in Sasak Tribe Bamboo Weaving - Antiqa Putri Salsabila; Pacu Suwar Ayu; Astrid Fitryani; M. Gunawan Supiarmo (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The bamboo weaving crafts of the Sasak tribe are a cultural heritage rich in aesthetic and functional values, behind which lie mathematical concepts that are indirectly applied by the artisans. The purpose of this research is to explore the mathematical concepts contained in the traditional bamboo weaving crafts of the Sasak tribe in Lombok, West Nusa Tenggara. The main focus of the research is to identify mathematical concepts in the shapes and motifs of traditional bamboo weaving crafts such as Tembolaq, Dedungki/Keben, Besek, and tampah or nyiru. This research is a qualitative study using an ethnographic method, which involves in-depth fieldwork, including direct observation of artisans during the weaving process, interviews with local craftsmen, and documentation of weaving patterns. The collected data were then analyzed descriptively to identify embedded mathematical ideas. The conclusion of this research is that the findings of mathematical concepts in the bamboo weaving of the Sasak Tribe consist of geometry and number pattern concepts. It is recommended that these mathematical elements be integrated into local mathematics education to strengthen cultural relevance and contextual learning.